Discussion - Of Mr. Howard's Paper on The Work of the Testing Department of the Watertown Arsenal, in Its Relation to the Metallurgy of Steel (see p. 223) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1909)
JAmes E. Howard, Watertown, Mass.:—In connection with this paper, it is the desire of the Watertown laboratory to receive suggestions as to the lines of work and the particular direction along which the examination of the ingot-metal should proceed, and any suggestions so offered will be noted with care, and the tests conducted so as to embrace such features as it is thought desirable to have investigated. To me the question of structural continuity seems of para-